The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12904-017-0226-8
|View full text |Cite
|
Sign up to set email alerts
|

Engaging patients and families to create a feasible clinical trial integrating palliative and heart failure care: results of the ENABLE CHF-PC pilot clinical trial

Abstract: Background: Early palliative care (EPC) is recommended but rarely integrated with advanced heart failure (HF) care. We engaged patients and family caregivers to study the feasibility and site differences in a two-site EPC trial, ENABLE CHF-PC (Educate, Nurture, Advise, Before Life Ends Comprehensive Heartcare for Patients and Caregivers).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 55 publications
0
106
0
Order By: Relevance
“…2,10,11 In light of this, we developed a nurse-led palliative care intervention for family caregivers of persons with advanced heart failure called ENABLE CHF-PC (Educate, Nurture, Advise, Before Life Ends Comprehensive Heart Failure for Patients and Caregivers), consisting of 4 weekly 20-to 60-minute manualized psychosocial and problem-solving support telephonic sessions facilitated by a registered nurse coach and a study team-developed Charting Your Course-Caregiver guidebook plus monthly follow-up for 48 weeks. After performing formative evaluation work to adapt the ENABLE caregiver intervention from cancer to heart failure and refine the intervention in 2 singlegroup pilot trials, 12,13 we performed a randomized clinical trial to test the effect of ENABLE CHF-PC compared with usual care. For our primary end points, we hypothesized that caregivers receiving the intervention would report better quality of life, improved mood (measured by anxiety and depressive symptoms), and decreased burden compared with usual care over 16 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…2,10,11 In light of this, we developed a nurse-led palliative care intervention for family caregivers of persons with advanced heart failure called ENABLE CHF-PC (Educate, Nurture, Advise, Before Life Ends Comprehensive Heart Failure for Patients and Caregivers), consisting of 4 weekly 20-to 60-minute manualized psychosocial and problem-solving support telephonic sessions facilitated by a registered nurse coach and a study team-developed Charting Your Course-Caregiver guidebook plus monthly follow-up for 48 weeks. After performing formative evaluation work to adapt the ENABLE caregiver intervention from cancer to heart failure and refine the intervention in 2 singlegroup pilot trials, 12,13 we performed a randomized clinical trial to test the effect of ENABLE CHF-PC compared with usual care. For our primary end points, we hypothesized that caregivers receiving the intervention would report better quality of life, improved mood (measured by anxiety and depressive symptoms), and decreased burden compared with usual care over 16 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…An example is the ENABLE model (Educate, Nurture, Advise, Before Life Ends), which has demonstrated effectiveness for oncology and heart failure. ( 28 ) The intervention included an in‐person PC assessment and weekly telehealth coaching sessions with advanced‐practice nurses for 6 weeks and 4 weeks for caregivers on select topics such as problem‐solving, symptom management, communication, and decision‐making. The qualitative programmatic evaluation found that participants gained illness management and decision‐making skills while continuing with curative treatments, reported feeling empowered, and experienced better care planning.…”
Section: Structures and Processes Required For Integrating Nonhospicementioning
confidence: 99%
“…9 Additional large-scale trials of the effect of PC interventions on patient and caregiver quality-of-life outcomes are now ongoing, and hopefully higherpowered data to support the PC-HF collaboration will be forthcoming. 10,11 Patients receiving MCS can experience high symptom burdens and have multifaceted advance care planning needs and complex end-of-life considerations that would benefit from ongoing PC-MCS collaboration. Patients with advanced illness often face a constellation of quality-of-life-limiting symptoms.…”
Section: Collaborative Care For the Duration Of Treatmentmentioning
confidence: 99%